Board governance mechanisms and sustainability reporting quality: A theoretical framework - Elaigwu Moses; Ayoib Che Ahmad; Salau Olarinoye Abdulmalik (Cogent Business & Management, 2020)
The presumed poor performance in terms of sustainability commitments and Sustainability Reporting Quality (SRQ) of quoted companies have incentivized stakeholders' agitation relating to the Economic, Environmental, and Social (EES) impacts of companies' operations. Business activities have generated several threats in the form of climate change, pollution, GHG emission as well as natural disasters, and several other problems that have negatively affected the environment and stakeholders. Companies are expected to report their sustainability performance to stakeholders. However, the quality of such sustainability reports has been critically criticized as they are mostly assumed to fall below stakeholders' expectations. This study aims to conceptually examine the association between board governance mechanisms and SRQ in Malaysia. The method adopted by this study is the review of previous literature on sustainability reporting practices and SRQ to gain insight into drawing a proposition regarding the relationship between board attributes and SRQ of PLCs in Malaysia. Through this method, the study generally verifies the SRQ of firms and how it is influenced by board attributes. Based on the insight from the reviewed past investigations, the study concludes in its proposition that there is a positive association between the examined board governance elements and SRQ based on multiple theories. The study has practical implications for the companies, regulators, government, and other stakeholders in their policy considerations and investment decisions. The study recommends an empirical study to re-investigate SRQ employing the variables used in this study and more board attributes to enhance the generalizability of the findings.
Keywords: 650; board governance mechanisms; sustainability reporting quality; economic impact; environmental impact; social impact; Malaysia